Incidence and risk factors of superficial and deep vein thrombosis associated with peripherally inserted central catheters in children. (12th October 2016) - Menéndez, J. J.; Verdú, C.; Calderón, B.; Gómez‐Zamora, A.; Schüffelmann, C.; de la Cruz, J. J.; de la Oliva, P.
Abstract : Essentials Pediatric studies on peripherally inserted central catheter (PICC)‐related thrombosis are scarce. This study analyzes incidence and risk factors for PICC‐related venous thrombosis in children. PICC‐related thrombosis is a common, and nearly always, asymptomatic complication. Echo‐guided insertion and a catheter to vein ratio < 0.33 may notably decrease this complication. Summary: Background: Upper‐extremity venous thrombosis is associated with the use of peripherally inserted central catheters (PICCs). Few pediatric studies have focused on this issue. Objectives: To determine the incidence and risk factors for PICC‐related superficial vein thrombosis (SVT) and deep vein thrombosis (DVT) in children. Patients/methods: An observational follow‐up cohort study was conducted at a single hospital between June 2012 and June 2015. All patients receiving a PICC were enrolled and followed up, with weekly Doppler ultrasound examination of the catheterized limb until PICC removal. Patient, procedural and follow‐up data were analyzed. Results: In the study period, 265 PICCs were inserted (median age of patients 6.5 years, interquartile range [IQR] 2.4–13 years; median weight 20 kg, IQR 11–38 kg; 54% males; 67.9% chronically ill), and patients were followed up for a total of 9743 days. The median indwelling time was 21 days (IQR 12–37 days). During follow‐up, 88 (33.2% of insertions) PICC‐related thromboses (incidence rate [IR] 9.03 per 1000 catheter‐days) were diagnosed, 66 (24.9%) as isolated SVT, seven (2.6%) as isolated DVT, and 15 (5.7%) as SVT with associated DVT (IR 6.78, 0.71 and 1.54 per 1000 catheter‐days, respectively). Only 9.9% of patients with SVT and 18.2% of those with DVT were symptomatic. The main risk factors for PICC‐related SVT and DVT were a catheter/vein ratio of > 0.33 and thrombosis of the catheterized superficial vein, respectively. Conclusions: PICC‐related thrombosis is a common and nearly always asymptomatic complication in children, the SVT rate being approximately three times higher than the DVT rate. Optimal vein and catheter selection, yielding the lowest possible catheter/vein ratio, may decrease the rate of PICC‐related thrombosis.